EDUCATIONAL TECHNOLOGIES AS A FACTOR OF DEVELOPMENT - Khujamberdiev Tursunpulat (European Journal of Humanities and Educational Advancements, 2023)
This article deals with some issues of modern ped-technologies applied to teaching social sciences in the course of reforms. Also, attention is paid to the possibilities of teaching social science, and the commonality of education and personal development is analyzed from today’s point of view.